The Effect of Online Education on Children’s Social Skills During the COVID-19 Pandemic - Günindi, Yunus (International Electronic Journal of Elementary Education, 2023)
This study aimed to determine if there is any difference in the social adaptation skills of five-year-old preschool children who did not receive any social skills intervention program besides the ongoing curriculum, but continued their education process in different environments (face-to-face/online) due to the pandemic. Included in the study were 296 children enrolled in independent kindergartens, who were within the five-year-old age group and were from similar socioeconomic families. The study included 159 children who were attended face-to-face education and 137 children who attended online education. At the beginning of their formal education, the Social Adaptation Skills Scale (SASS) was administered to the children in both groups as a pre-test. At the end of the trimester, the SASS was repeated as a post-test. There was a significant difference between the face-to-face education group and the online education group, in favor of the face-to-face education group, in terms of the social adaptation sub-factor of the SASS. Moreover, the social incompatibility sub-factor scores of the face-to-face education group were significantly lower than those of the children in the online education group.